Proof of a conjecture of Xiao and Zamora - Chen, Wanfang; Lu, Changhong; Yang, Jia-Bao; Yuan, Long-Tu (Graphs and combinatorics, 2025)
A wheel, defined by Tutte, is the graph obtained from a circle by adding one new vertex and joining this vertex to all vertices of the circle. We determine the maximum number of edges in a graph which does not contain vertex-disjoint wheels. This confirms a conjecture posed by Xiao and Zamora in a stronger form.